Fabrication and Thermo-Mechanical Characterization of HEMA Treated UV Photo-Cured Biodegradable Chitosan Film - Dey, Kamol; Alamgir, Poonam; Mohol, Gulshana; Parvin, Shahnaz; Khan, Mubarak A.; Khan, Ruhul A. (Journal of Research Updates in Polymer Science, 2014)
Chitosan was extracted from dried prawn shell via chitin and was characterized by Fourier Transformed Infrared (FTIR) Spectroscopy. Thin film of chitosan was prepared by solution casting using a 2% chitosan solution. Chitosan was dissolved in 2% acetic acid. Mechanical properties like tensile strength (TS) and elongation at break (Eb%) of chitosan film were studied. Eight formulations (M1: 5% HEMA to M8: 40% HEMA) were developed with 2-hydroxyethyl methacrylate (HEMA) monomer in methanol (MeOH) along with photoinitiator Darocur-4043 (2%). The film was soaked in those formulations for 1 min and cured under UV radiation at different radiation intensities for the improvement of physico-mechanical properties of the film. The cured films were then subjected to various characterization tests like TS, Eb%, water absorption, FTIR spectroscopy, polymer loading (PL), differential thermal analysis (DTA), and thermo gravimetric analysis (TGA). The M6 formulation containing 30% HEMA in MeOH solution showed the best performance at 20th UV pass. The highest TS, Eb% and PL were found to be 31 MPa, 71.25% and 26.38%, respectively, for the same formulation at 20th UV pass. The DTA/TGA study showed that the film with M6 formulation at 20th UV pass was thermally more stable than non-radiated chitosan film. The FTIR analysis revealed the crosslinking between HEMA and chitosan.